A Review of Success Factors Behind Community Action Research Program (CARP): A Case of Experiences From Smallholder Dairy Farmers of Lushoto in Tanzania - Liliane Pasape (Journal of Participatory Research Methods)
This article details steps, strategies, methods, and tools used during the project formulation, implementation, monitoring, evaluation, and closure of a livestock CARP conducted in the Lushoto district of Tanzania's Tanga Region. According to the study, CARP is a successful approach to managing agriculture-related community projects because it allows for the active participation of community members and all stakeholders, resulting in a sense of ownership and assurance of project success and sustainability. However, this work established that in order for the CARP to produce desirable results, a robust framework for organization and implementation must be in place; optimal methods of involving multiple stakeholders must be used; and strategies to ensure its sustainability must be set and agreed upon by all implementers during the implementation period.